(untitled) (The Research of Medical Science Review, 2025)
Background: Online education has become increasingly prevalent, offering flexible learning opportunities. However, factors like cognitive load and self-efficacy significantly influence student performance and adaptation in virtual environments. Objectives: This study aimed to examine the relationship between general self-efficacy and cognitive load in online learning among undergraduate physical therapy students. It also explored how COVID-19-related stress and physical activity levels interact with cognitive load. Methods: A cross-sectional study was conducted from October 2021 to July 2022 involving 444 undergraduate physical therapy students from private universities, selected through non-probability convenience sampling. Inclusion criteria required students to have at least six months of online learning experience. Data were collected using the General Self-Efficacy Scale, Cognitive Load Scale, International Physical Activity Questionnaire, and COVID-19 Stress Scale. An online form was distributed, and responses were analyzed using SPSS version 23. Results: Findings revealed a weak positive correlation between cognitive load and general self-efficacy (r = 0.358, p = 0.486). Additionally, cognitive load showed weak positive correlations with COVID-19 stress (r = 0.151, p = 0.001) and physical activity (r = 0.111, p = 0.019). These results indicate that although the associations are not strong, they are statistically relevant in the context of online education. Conclusion: The study suggests that enhancing self-efficacy may help reduce cognitive load among students engaged in online learning. Meanwhile, COVID-19-related stress may contribute to increased cognitive burden. Promoting self-efficacy and addressing stress management could support better learning outcomes in virtual settings.